COST PERFORMANCE ANALYSIS USING EARNED VALUE METHOD ON PRESERVATION OF EXIT TOLL ROAD SECTION 5 PANDAAN MALANG - Mughni, Amalia Fathimah Azh Zhahra; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2023)
The development of road or toll road infrastructure in a country can be used as a benchmark to determine the level of economic progress of a country, both macro and micro. The location of toll exits has a significant effect in absorbing labor and creating new business activities. Projects are dynamic, so contractors must be responsive to changes in situations and conditions on the project, if they want to succeed in reaping optimum profits. Aspects of planning a highly competitive construction at this time are very demanding on accuracy, effectiveness, efficiency, and economy in analyzing a project. In the world of construction projects, there are many things that can be done, one of which is cost control. In controlling costs, efforts can be made so that the realization of costs that occur is in accordance with the needs of implementation and is not excessive, such as cost suppression efforts, namely making savings without reducing quantity or quality. The Earned Value Method is used to determine project performance in terms of costs at one time, determine project performance in terms of schedule/time at one time, estimate costs to complete the project after the evaluation time and estimate the time to complete the project after the evaluation. In this research the author carried out a cost analysis using the Earned Value Method on the preservation of the Section 5 Pandaan Malang Toll Exit Road.